ASCEND-8 pharmacokinetic, safety, and efficacy data for ceritinib 450 mg with food in patients with anaplastic lymphoma kinase–positive non-small cell lung Cancer: A clinical perspective. (2019) - Otoukesh, Salman; Sanchez, Tiffany; Mirshahidi, Saied; Wallace, Desiree; Mirshahidi, Hamid
Highlights: The FDA-approved dosage of ceritinib was changed in 2017–450 mg taken with food. The new dosage may reduce gastrointestinal adverse events and dose modifications. Prescribing ceritinib 450 mg with food may positively impact patient management. Abstract: Anaplastic lymphoma kinase–positive ( ALK +) non-small cell lung cancer (NSCLC) is diagnosed in up to 126, 000 patients worldwide annually. Ceritinib is a next-generation ALK-targeted tyrosine kinase inhibitor that is approved for the treatment of patients with metastatic ALK + NSCLC. In December 2017, the US Food and Drug Administration–approved dose of ceritinib was changed from 750 mg/day under fasting conditions to 450 mg/day taken with food for the treatment of patients with ALK + NSCLC. This change was implemented on the basis of data from studies designed to investigate ways to reduce the frequency of gastrointestinal adverse events noted in patients enrolled in several ASCEND clinical trials that evaluated a ceritinib 750-mg fasted dose as either first- or second/third-line treatment. This review highlights and discusses published findings from the ASCEND-8 food-effect trial and includes commentary from physicians regarding their own clinical cases of patients who were enrolled in the trial and treated with either the 750-mg fasted or 450-mg fed dose of ceritinib. The review also discusses the implications of using the recently approved ceritinib 450-mg dose in the clinical setting.